COMPARATIVE ANALYSIS OF MODERN METHODS FOR TEACHING SWIMMING TO ADULTS - Artegov P.D.; Akatova A.A.; Legotkin A.N.; Legotkina L.R. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to determine the methodological features of teaching swimming to adults based on theoretical analysis. Methods and structure of the study. An analysis of scientific, methodological and Internet sources was performed to identify an effective methodology for teaching swimming to adults, where the criterion is the time of training or the time period of training. The sample consisted of scientific publications presented on the websites of the library systems library and cyberleninka for the period 2006-2024. Results and conclusions. In the course of the study, it was determined that the main distinctive feature in teaching swimming to adults is the emphasis on the psychological side of the educational and training process. At the same time, special attention is paid to teaching correct breathing. From all the diversity presented in the literature and the Internet, two main methods of teaching swimming stand out: the traditional method – teaching swimming 1-2 styles, and the complex method – teaching swimming all four styles.